The history of the Brethren - Noel, Napoleon L. 1853-1932 (Denver, CO W.F. Knapp, 1936)
Contents : vol. 1 : includes biographical notes, Chapters 1-7. Includes bibliographical references. Index included in vol. 2.
Copy one donated by Mr R.E. Glasgow
Keywords: Brethren movement -- Exclusive Brethren -- church history